The moon that turns you back - Alyan, Hala, 1986- (Ecco, an imprint of HarperCollins Publishers, 2024)
A diaspora of memories runs through this poetry collection--a multiplicity of voices, bodies, and houses hold archival material for one another, tracing paths between Brooklyn, Beirut, and Jerusalem. Boundaries and borders blur between space and time and poetic form--small banal moments of daily life live within geopolitical brutalities and, vice versa, the desire for stability lives in familiarity with displacement. These poems take stock of who and what can displace you from home and from your own body--and, conversely, the kind of resilience, tenacity, and love that can bring you back into yourself and into the context of past and future generations. Hala Alyan asks, What stops you from transforming into someone or something else? When you have lived a life in flux, how do you find rest?